The soup cleanse : a revolutionary detox of nourishing soups and healing broths from the founders of Soupure - Blatteis, Angela; Vella, Vivienne; Holtzman, Rachel (Grand Central Life & Style, 2015)
"When Angela Blatteis and Vivienne Vella set out to create Soupure, the LA-based soup company at the forefront of the souping movement, they wanted to share the power of healing soups with the world. With a few simple, delicious recipes they've helped people lose weight, boost their energy, and feel better every day. Now with THE SOUP CLEANSE they are bringing their satisfying, 100 percent good-for-you, whole food-based soups straight into your kitchen. With more than 50 delicious recipes and a flexible, easy-to-follow detox program, you'll learn how to nourish and purify your body while flooding it with essential nutrients. You will sip your way through high-fiber soups packed full of regenerative whole food ingredients. Unlike juicing and many other quick-fix diets, THE SOUP CLEANSE is built on simple, satisfying recipes that won't leave you feeling hungry or deprived, making it accessible and easy to stick to-even for those with the busiest lifestyles. Get ready to rejuvenate, revitalize, and reclaim your health-one sip at a time!,"--Amazon.com.